Internet, social media, and smartphone addiction as elements of addictive behavior in adolescents - Fedorciv, Ольга; Чорномидз, Андрій; Chornomydz, Ірина; Chornomydz, Юрій (Psychosomatic Medicine and General Practice, 2025)
Background. The problem of addictive behavior among adolescents is reaching alarming proportions, especially in the context of the socio-ecological crisis and the state of war in Ukraine. Excessive use of the internet, smartphones, and social media poses a serious threat to the mental and physical health of the younger generation, which requires in-depth scientific analysis. Objective. To analyze the scientific literature on the problem of internet addiction as a form of addictive behavior in adolescents, and to systematize data on its prevalence, forms, causes, clinical manifestations, and consequences. Results. The data analysis showed that internet addiction is a complex concept that includes addiction to social media, online games, cybersexual addiction, and other forms. The prevalence of internet addiction among adolescents worldwide varies widely, reaching 64% in some regions, and up to 52% in Ukraine. Adolescence is a critical period for the formation of addictions due to psychological characteristics: the desire for new experiences, fear of responsibility, and the search for self-affirmation. The main causes of addiction development include a deficit of communication within the family, low self-esteem, and a lack of friends and hobbies. The consequences include both psychological problems (depression, apathy, social maladjustment) and physical disorders (sleep disturbances, vision and posture problems). It has been established that an authoritative parenting style characterized by warmth in relationships can reduce the risk of addiction development. Conclusions. Internet addiction is a global and multifaceted problem that requires an interdisciplinary approach. Further study of its formation mechanisms and the development of effective prevention and correction programs adapted to modern conditions are necessary. Keywords: addictive behavior, internet addiction, adolescents, smartphone, social media, mental health, prevention УДК 616.89-008.44:[004.738.5:613.86]-053.6